Utilizing Lipid Bond Technology With Molecular Lipid Complex to Provide Lipid Treatment for Damaged Hair - Nam Hai Lai; Thi Hong Ngoc Dang; Thu Thuy Nguyen; Duong Thuc Quyen Phan (Dermatology Research and Practice)
Human hair fibers are mainly composed of proteins, lipids, and water. In particular, lipids play an important role in keeping hair healthy, stabilizing its structure, affecting shine, feel, manageability, and strength. In addition to each person’s physical condition and constitution, the cause of reduction and loss of hair lipids also comes from external causes such as UV, pollution, and specially styling chemicals. A decrease in hair lipid content correlates with reduced tensile strength, diminished shine, increased breakage, and hair damage. In this study, we focus on Lipid Bond Technology with small molecule real lipids derived from plant oil triglycerides, known as 369LAB Lipid Bond, reverse chemical and environmental damage by restoring lipid bonds in hair, regenerates hair structure, and improves hair strength. Research results show that 369LAB Lipid Bond has an average particle size of 39.83 nm, helping to penetrate deeply into the hair; replace lost lipids, restore lipids to damaged hair. After one use, the total amount of lipid restored is equivalent to natural hair before damage. It is nonsticky and does not clog hair follicles. SEM images show morphological improvement in the integrity of the epidermis and regeneration of lipid layers immediately, with lasting repair even after discontinuation of use. The amount of force that breaks individual hair strands in testing shows that 369LAB Lipid Bond makes hair stronger. The Lipid Bond Technology not only strengthens hair while using the product but also maintains its healthy resilience long after. The current research will provide the breakthrough for new applications in cosmetic, skin, and hair care products, to address the remaining difficulties and challenges in the treatment of damaged hair.